2016
DOI: 10.1002/gea.21564
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Sourcing of Flint Artifacts from Western Belgium and the German Rhineland: Testing Hypotheses on Gravettian Period Mobility and Raw Material Economy

Abstract: Identifying the geological and geographical origin of lithic raw materials is critical to effectively address prehistoric forager raw material economies and mobility strategies. Currently, Paleolithic archaeology in Belgium lacks a systematic sourcing strategy to effectively substantiate detailed interpretations of prehistoric hunter‐gatherer behavioral change across time and space. This pilot study evaluates the potential to “fingerprint” flint from the Mons Basin, western Belgium, using the laser ablation‐in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 41 publications
1
43
0
2
Order By: Relevance
“…The use of geochemical studies to characterise chert have increased in the last few years [1][2][3][4][5][6][7][8]. Results show that these analyses are essential for better determining the relationship prehistoric human populations had with their environment.…”
Section: Introductionmentioning
confidence: 94%
“…The use of geochemical studies to characterise chert have increased in the last few years [1][2][3][4][5][6][7][8]. Results show that these analyses are essential for better determining the relationship prehistoric human populations had with their environment.…”
Section: Introductionmentioning
confidence: 94%
“…The results of sensitive LA-ICP-MS elemental/isotopic measurements can be used to support the use of other instrumental meth- ods such as Scanning Electron Microscopy with Energy Dispersive X-Ray Spectrometry (SEM-EDS) [12,31,38,74,79,112,118,130,135,166,170,181,182], Electron Probe Microanalysis (EPMA) [75, 80, 81, 97, 112, 167, 183 -185], X-Ray Fluorescence (XRF) [16,31,35,44,93,94,98,119,120], Proton Induced X-Ray Emission [22,41,95,114,186,187] or Neutron Activation Analysis (NAA) [23, 36, 99, 100, 107, 108, 114, 146, 188 -192]. Leroy et al [193] reported the first application of confocal Synchrotron Radiation micro X-Ray Fluorescence (SR-m-XRF) with LA-ICP-MS.…”
Section: Multi-technique Approach Incorporating La-icp-msmentioning
confidence: 99%
“…Whereas archaeological studies mostly focus on typological classification, lithic technology, and functional analysis of flint artifacts (Andrefsky, ; Odell, ), geological research focusses on the petrological and geochemical aspects as well as the formation process of flint (Bustillo et al, ; Madsen & Stemmerik, ; L. Moreau et al, ; Zijlstra, ). The combination of both disciplines is necessary to have a full understanding and an integrated approach which will lead to novel results and insights.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the geochemistry of flint, researchers commonly use X‐ray fluorescence (XRF) for elemental analysis (e.g., Gauthier & Burke, ; Gauthier, Burke, & Leclerc, ; L. Moreau et al, ; Olivares et al, ). The sample size is limited by the sample chamber in the case of benchtop XRF, therefore, sample preparation could be required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation